THE EFFECT OF INDEX CARD MATCH LEARNING MODEL ON STUDENTS’ INTEREST ON SCIENCE MATERIAL AT VII CLASS - Berlian, Zainal; Purnamasari, Rita; Samiha, Yulia Tri; ., Syarifah (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
This study aims to determine the effect of learning model of Active Learning type of Index Card Match on student's interest in science class VII MTs. This research is a kind of quantitative research. Sampling in this research is done by purposive technique sampling which considering certain criteria based on the value of both classes taught by the same teacher. The sample of research taken by class VII.D and VII.E. This study was conducted during two meetings with the assessment instrument in the form of a questionnaire (posttest). The questionnaire was a questionnaire of students' interest in learning by shaving four indicators of student interest in learning: student interest, student attention, student involvement and feelings of pleasure. The results of this study indicate that students' interest in achievement of student interest indicators obtained 90.27%. In the indicator of student attention for the experimental class obtained 90.10%. Indicator of student involvement in the experimental class was 89.86%. The last indicator of the feeling of pleasure in the experimental class is 91.55%. The result of the research also shows that based on tcount 4,913> ttabel 1,993 and significance value <0.05, Ha is accepted and H0 is rejected. The average score of students' interest in the control class is 63,205 and the experimental class is 68,805. In the four indicators of interest in learning are interest, attention, involvement, and feelings of pleasure, the percentage of the experimental class is higher than the control class. Therefore it is expected that the active learning model of index card match type can be used as a learning model because with this model the students will be more active in their activities so that their learning interest can grow and be maintained.Keywords: active learning, index card match, learning model